Partial splenic embolization - Hiroshi Yoshida; Yasuhiro Mamada; Nobuhiko Taniai; Takashi Tajiri (2007)
Partial splenic embolization (PSE) is a non-surgical procedure developed to treat hypersplenism as a result of hepatic disease and thus avoid the disadvantages of splenectomy. A femoral artery approach is used for selective catheterization of the splenic artery. Generally, the catheter tip is placed as distally as possible in an intrasplenic artery. After an injection of antibiotics and steroids, embolization is achieved by injecting 2-mm gelatin sponge cubes suspended in a saline solution containing antibiotics. PSE can benefit patients with thrombocytopenia, esophagogastric varices, portal hypertensive gastropathy, encephalopathy, liver dysfunction, splenic aneurysm, and splenic trauma. The contraindications of PSE include secondary splenomegaly and hypersplenism in patients with terminal-stage underlying disease; pyrexia or severe infections are associated with a high risk of splenic abscess after PSE. Complications of PSE include daily intermittent fever, abdominal pain, nausea and vomiting, abdominal fullness, appetite loss, and postembolization syndrome. Decreased portal-vein flow and a rapid increase in the platelet count after excessive embolization may cause portal-vein or splenic-vein thrombosis.